PROFIL PASIEN SINDROM TEROWONGAN KARPAL DI POLIKLINIK SARAF RSUP SANGLAH DENPASAR - I Komang Arimbawa; Ni Komang Dewi Mahayani; I Gusti Ngurah Purna Putra; Thomas Eko Purwata (NEURONA, 2018)
PROFILE OF PATIENT CARPAL TUNNEL SYNDROME IN THE NEUROLOGY CLINIC SANGLAH GENERAL HOSPITAL IN DENPASARABSTRACTIntroduction: Carpal tunnel syndrome (CTS) is the entrapment of the median nerve at the carpal tunnel.Aims: To determine the profile of patients with carpal tunnel syndrome in the Neurology Clinic Sanglah GeneralHospital in Denpasar.Methods: This is a descriptive, cross sectional study. Data was collected during a6-month period from April 2016 to September 2016.Results: Among 25 subjects, 76% were female with mean age 48+10,133 years old, housewives (40%), with working hours of more than 8 hours per day. Most subjects had symptoms on the right hand 68% in the form of tingling sensation (96%), pain (36%), numbness (48%), and hand weakness (24%). Most subject has positive Phalen test (80%), Tinnel (80%), and Flick (76%) and small number had tenar muscle atrophy (28%), impaired sensibility (32%), and decrease in muscle strength (24%). As many as 68% of subjects had distal sensoric latency of median nerve recorded on the 4th digit>3.5msec, while 72% showed ≥0.5 difference of distal sensoric latency between the median nerve and ulnar nerve, while8% showed no response.Discussion: Most patients were female, with dominant complaint was tingling, positive Phalen and Tinnel test, and68% ENMG result shown CTS.Keywords: Carpal tunnel syndrome, electroneuromyography, patient profileABSTRAKPendahuluan: Sindrom terowongan karpal (STK) adalah penjepitan N. Medianus saat melewati terowongan karpal. Tujuan: Untuk mengetahui profil pasien sindrom terowongan karpal di poliklinik saraf RSUP Sanglah, Denpasar. Metode: Penelitian potong lintang terhadap pasien dengan STK yang berobat ke poliklinik saraf RSUP Sanglah,Denpasar secara konsekutif pada bulan April-September 2016.Hasil: Dari 25 subjek, 76% adalah perempuan dengan rerata usia 48+10,133 tahun, ibu rumah tangga (40%) dengan durasi kerja lebih dari 8 jam perhari. Mayoritas keluhan terjadi pada tangan kanan (68%), berupa kesemutan (96%), nyeri (36%), rasa tebal (48%), dan kelemahan otot  tangan (24%). Sebagian besar hasil positif pada tes Phalen (80%), Tinnel (80%), dan Flick (76%), serta sebagian kecil mengalami atrofi otot tenar (28%), gangguan sensibilitas (32%), dan kelemahan otot tangan (24%). Latensi distal sensorik N. Medianus pada perekaman jari IV terutama >3,5ms (68%), perbedaan latensi distal sensorik N. Medianus dan Ulnaris ≥0,5ms (72%), dan tidak ada respons 8%.Diskusi: Sebagian besar sampel adalah perempuan, gejala yang dominan berupa kesemutan, tes Phalen dan Tinnel yang positif, serta hasil ENMG 68% menderita STK.Kata kunci: Elektroneuromiografi, profil pasien, sindrom terowongan karpal